New Insights into the Calcium Flux Used in Ancient Longquan and Yue Kilns Based on Strontium Isotopic Compositions. (21st September 2018) - Ma, H.; Wood, N.; Doherty, C.; Zheng, J.; Zhou, G.; Duan, H.
Abstract : The glazes of seven types of greenware produced in the Yue and Longquan kilns between the Tang dynasty and the Ming dynasty (ad 618–1644) were studied for their strontium isotopic compositions and bulk chemical compositions. The aim was to identify the raw materials used as the calcium fluxes in the glaze recipes and whether the raw materials changed over time, particularly before and after the Southern Song dynasty (ad 1127–1279). From this work, botanic ash has been identified as the raw material used as the calcium flux in all the seven glaze types studied, and some related ceramic historical issues are also discussed.